Factors on the distribution, migration, and leaching of potential toxic metals in the soil and risk assessment around the zinc smelter. (November 2022) - Xie, Qing; Ren, Bozhi; Shi, Xiyang; Hursthouse, Andrew
Highlights: Relations between pH, depth, and PTEs concentration in weakly alkaline red loam. Comparison of migration ability of Pb, Cr, As, Cd, and Sb in the soil. Relationships between leaching concentration, depth, and total concentration of soil PTEs. Comparison of risks to humans and the ecological environment of PTEs in the soil. Abstract: Mining activities usually caused soil polluted by potential toxic elements (PTEs). This paper used the analysis of correlation, variance, and power analysis to clarify the relationship and migration characteristic of 90 samples in 30 sampling points at the depths of 30, 100, and 200 cm. The results showed in the weakly alkaline red loam, pH had no significant effect on the total concentration of PTEs in the soil. The greater the depth was, the greater the total concentration of PTEs in the soil. And depth had no significant effect on the soil pH. The cadmium (Cd) migration process in the soil was more severe than other elements. The arsenic (As) migration ability was lower than other elements. Except for chromium (Cr), lead (Pb) and antimony (Sb) had the strongest migration ability. Soil depth and total PTEs concentration had no significant effect on the leaching concentration of As and Sb, whether it was by water leaching or acid leaching. From the perspective of the potential ecological risk index, Pb and Cr had low or no risk, while As, Sb, and Cd needed to be dealt with. From the perspective of Hazard Quotient, Pb, Cr, and Cd have low or no non-carcinogenic risk, while As and Sb did the opposite. This research inspired understanding the process of soil PTEs migration, and helping local government to control the distribution of PTEs.